Assessment of Blood Pressure Control Status Among Hypertensive Patients Attending Rwandan District Hospital NCD Clinics: A Retrospective Follow-Up Study - Evariste Ntaganda; Ziad El-Khatib; Regine Mugeni; Boniface Nsengiyumva; Clarisse Musanabaganwa; James Gafirita; Francois Uwinkindi; Richard Kalisa (Journal of Epidemiology and Global Health)
Abstract Background Hypertension is a major public health issue and a leading risk factor for cardiovascular disease (CVD). We assessed blood pressure (BP) control among adult hypertensive patients attending non-communicable disease (NCD) clinics in five Rwandan district hospitals. Methods We extracted data on hypertensive management from five Rwandan district hospitals from June 2016 to August 2021. BP control was defined as systolic blood pressure (SBP) < 140 mmHg and diastolic blood pressure (DBP) < 90 mmHg measured within the last four months. We performed statistical analysis using chi-square tests and multivariate regression analyses with 95% confidence intervals (CI). Results Blood pressure control was achieved in 41.5% of hypertensive patients (n = 438/1,055). The majority were aged > 60 years (mean age 62; n = 663/1,055; 62.8%), and women, with approximately three-quarters of patients (n = 796/1,055; 75.5%) had a BMI between 18.5 and 24.9 Kg/m2 and the majority (n = 843/1,055; 79.9%) resided in rural districts. More than half (n = 585/1,055; 55.5%) were taking two antihypertensive medications. Factors significantly associated with uncontrolled BP included BMI ≥ 30 kg/m2 (p < 0.001), use of Angiotensin-converting enzyme (ACE) inhibitors (p = 0.01), use of four antihypertensive drugs (p = 0.013), and missing an NCD clinic appointment (p < 0.001). Conclusions BP control rates among hypertensive patients attending NCD clinics remain low. Strengthening patient counseling, encouraging physical activity, and improving medication adherence are critical. Building the capacity of healthcare staff at both hospital and health centre levels is vital to improving hypertension management in NCD clinics.